Relationship between visuospatial episodic memory, processing speed and executive function: are they stable over a lifespan? - Bruna Fulgêncio Dias; Letícia Oliveira Rezende; Leandro Fernandes Malloy-Diniz; Jonas Jardim de Paula (Arquivos de Neuro-Psiquiatria)
ABSTRACT The present study evaluated the association between episodic memory, executive function and processing speed in a sample with different age ranges. We tested the hypothesis that processing speed, executive function and memory are more strongly associated during childhood and old age. We evaluated 571 participants, aged six to 92 years, divided into four age groups: children/adolescents, young adults, middle-aged adults and older adults. Correlation analyses suggested that the shared variance between the processing speed and memory is strong in childhood but weak across other age ranges. Executive function, however, had a stronger association both in childhood and in old age, when compared with the intermediate stages. We conclude that the effects of processing speed and executive function on memory are not stable across human development. These functions may be compensatory mechanisms for memory functioning in childhood and old age.